SISTEM INFORMASI PELAYANAN ADMINISTRASI BERBASIS WEB PADA DESA GLEMPANG MAOS - yustina meisella kristania (Indonesian Journal of Networking and Security (IJNS), 2022)
Human dependence on information is increasing to meet these factors, it takes the computer because of the tools of high-speed and very accurate in processing the data. Kelurahan Glempang is located on Jln. Raya Glempang-Maos. Glempang is a Kelurahan office that is engaged in the service of population. In processing the application of letters relating to the administration of population services is still less accurate and efficient, as a result in completing service activities was less effective and longer. Software development method used is a waterfall model of urban village analysis, which then forwarded the design, code generation, testing, and support or maintenance with the creation of the website. While the data collection techniques used are observation, interview and studipustaka. With the website of urban service information system as a means of service for the community and facilitate the service of application letter related to the administration of population, provide information to the community, as well as facilitate data storage. Kelurahan website can also be used as a means to communicate between urban villages and citizens.